Factibilidad de la gestión del talento humano ajustado a la norma ISO 9001 - 2015 en la “Cooperativa de ahorro y crédito Artesanos Ltda.” - Burgos Amaya, Juan Carlos (2020)
This study formulates the feasibility for the application of a Quality Management model based on the ISO 9001-2015 Standard for the Human Talent Area of the Cooperativa de Ahórro y Crédito Artesanos Ltda., With a systematic focus on processes, based on risks , in order to achieve high quality standards in customer and partner service, with the contribution of the company's senior management. The management of the processes as a whole will be worked with a complete risk based approach, aimed at taking advantage of opportunities and avoiding unwanted results. The reason for this study is to evaluate the Management of the Human Talent Area and sustain the feasibility of implementing the quality management system based on the ISO 9001: 2015 standard, for which it will be verified if the processes meet the management parameters of quality, by collecting management indicators to determine if the Area is being successful or if there are weaknesses. The application of these parameters allows a better visualization of the processes. To obtain the information, the survey and interview techniques will mainly be used through the application of an online questionnaire, which is structured in such a way that it allows having a 360 vision of the area's strengths, opportunities, weaknesses and threats. \; a check list will be applied to determine if the information in the Area complies with the requirements of ISO 9001-2015\; the data obtained will serve as input for the determination of this project.